Application of augmented reality in the linguistic and literary education of primary school students - Liudmyla L. Nezhyva; Svitlana P. Palamar; Olha V. Kotenko; Liudmyla A. Nazarenko; Maryna S. Naumenko (Academy of Cognitive and Natural Sciences, 2024)
This paper explores the application of augmented reality (AR) technology in primary school students' linguistic and literary education. A review of current research on AR in education is presented, including studies on AR books for literacy instruction and reading motivation. The benefits of AR for enhancing students' reading comprehension, critical thinking, and imagination are discussed. AR features are analysed in new "Living Alphabet" books used in Ukrainian schools. The development of a mobile AR application for interactive reading lessons on fairy tales is detailed; this app allows students to actively engage with literary characters and settings in an immersive 3D environment. Pedagogical models employing AR applications, games, and theatre activities are proposed to improve literary reading instruction and foster key competencies aligned with the Ukrainian New School curriculum. The paper concludes that when thoughtfully implemented, AR technology can enrich primary students' linguistic and literary learning. Further research is recommended to prepare teachers to integrate AR into language arts instruction.